Distinct genetic structure in populations of Chrysoperla externa (Hagen) (Neuroptera, Chrysopidae) shown by genetic markers ISSR and COI gene - Barbosa, Nara C. C. P. [UNESP]; Freitas, Sérgio De [UNESP]; Morales, Adriana C. [UNESP] (Sociedade Brasileira de Entomologia, 2014)
Distinct genetic structure in populations of Chrysoperla externa (Hagen) (Neuroptera, Chrysopidae) shown by genetic markers ISSR and COI gene. Green lacewings are generalist predators, and the species Chrysoperla externa presents a great potential for use in biological control of agricultural pests due to its high predation and reproduction capacities, as well as its easy mass rearing in the laboratory. The adaptive success of a species is related to genetic variability, so that population genetic studies are extremely important in order to maximize success of the biological control. Thus, the present study used nuclear (Inter Simple Sequence Repeat - ISSR) and mitochondrial (Cytochrome Oxidase I - COI) molecular markers to estimate the genetic variability of 12 populations in the São Paulo State, Brazil, as well as the genetic relationships between populations. High levels of genetic diversity were observed for both markers, and the highest values of genetic diversity appear associated with municipalities that have the greatest areas of native vegetation. There was high haplotype sharing, and there was no correlation between the markers and the geographic distribution of the populations. The AMOVA indicated absence of genetic structure for the COI gene, suggesting that the sampled areas formed a single population unit. However, the great genetic differentiation among populations showed by ISSR demonstrates that these have been under differentiation after their expansion or may also reflect distinct dispersal behavior between males and females.
Keywords: genetic distance; Green lacewings; Insecta; population structure; variability